The content of clay soil planted with capsicum changed from some major nutrients according to a proposed model for a fertilizer equation - قشعور , بنان; سوسن عبدالله هيفا; أمجد حسن بدران; نصر شيخ سليمان (Latakia University Journal -Biological Sciences Series, 2022)
The experiment was carried out in the village of Beit al-Marj in the Qadmous region, during the year 2019, in clay soil planted with capsicum, where seven fertilization treatments of nitrogenous, phosphate and potassium fertilizers were studied, with the presence and absence of organic fertilizers, and under open field conditions. The results showed that the two treatments T1, T7 were significantly superior to all the studied treatments in providing the pepper plant requirements of nutrients, and in contrast, the increase in the amount of nitrogen fertilizer added in the T7 treatment led to an increase in the encouragement of the vegetative growth of the capsicum plant and the delay in entering the flowering stage compared to the rest of the studied treatments. , while the soil content of nutrients available to the capsicum plant decreased in the T3 treatment due to the absence of organic fertilization. As a result, it appeared that the T1 treatment in the conditions of clay soil was one of the best studied treatments as it contributed to raising the fertility of the soil, with the optimal use of fertilizers, and without the occurrence of environmental pollution or soil salinity.